PENATALAKSANAAN PASIEN DENGAN STEMI DI RUMAH SAKIT DAERAH: LAPORAN KASUS: PATIENT TREATMENT WITH STEMI IN RURAL HOSPITAL: A CASE REPORT - Siti Tari Salsa; Taufiqurrahman; Khairani Putri (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Coronary Arterial disease or Coronary heart disease (CHD) is a disease caused by partial or complete plaque buildup in the coronary artery lining, which causes blood flow blockage, thereby reducing oxygen supply to the heart muscle. Patient summary: A 74-year-old male patient came to Muda Sedia Regional General Hospital complaining of severe pain in the center of his chest for 8 hours prior to admission. The pain appeared suddenly when the patient woke up and was about to go to the bathroom. The pain was felt in the center of the chest, as if being pressed by a heavy object, radiating to the back and left arm for approximately 30 minutes. The pain did not subside or disappear with rest. The location of the pain could not be pinpointed with a single finger and was not affected by the patient's position. The patient did not complain of shortness of breath, nausea, or weakness. There was no coughing, vomiting, or fever. Physical examination of the heart and lungs was within normal limits. The ECG showed ST elevation in leads II, III, aVF, V4-V5, and laboratory results showed an increase in LDL cholesterol and a decrease in HDL. Cardiac enzyme tests showed an increase in troponin. Based on clinical findings, vital signs, physical examination, and laboratory results, the patient was diagnosed with inferolateral STEMI onset 8 hours prior. Given the patient's condition, the patient was immediately referred for urgent primary PCI. AbstrakPenyakit arteri Penyakit Jantung Koroner (PJK) atau Coronary Heart Desease (CHD) adalah penyakit akibat penumpukan plak sebagian atau seluruhnya di dalam lapisan arteri koroner, yang menyebabkan penyumbatan aliran darah sehingga suplai oksigen ke otot jantung berkurang. Penyempitan dan penyumbatan lapisan arteri koroner tersebut dikenal dengan istilah aterosklerosis yang menyebabkan sirkulasi oksigen ke jantung dan keluar jantung tidak adekuat. Keadaan tersebut dapat menimbulkan gejala nyeri dada, rasa berat dan tertekan di dada, nyeri ulu hati, mual muntah, keringat dingin, rasa terbakar sekitar dada, dan mudah lelah sehingga sulit melakukan aktivitas sehari – hari. Resume pasien, Pasien laki-laki usia 74 tahun datang ke RSUD Muda Sedia dengan keluhan 8 jam SMRS pasien merasakan nyeri hebat pada bagian tengah dada. Nyeri muncul secara tiba-tiba saat pasien bangun tidur dan hendak ke kamar mandi. Nyeri dirasakan di bagian tengah dada seperti dihimpit benda berat, menjalar ke punggung dan lengan kiri dengan durasi lebih kurang 30 menit. Nyeri tidak berkurang dan tidak hilang dengan beristirahat. Lokasi nyeri tidak dapat ditunjuk dengan satu jari dan tidak dipengaruhi posisi. Selain itu os juga mengeluhkan nyeri ulu hati disertai rasa tidak nyaman di perut. Pasien tidak mengeluhkan sesak nafas, mual, lemah. Tidak ada batuk, muntah, demam tidak ada.